AMC-integrated reconfigurable beamforming antenna by using RF-MEMS / Herwansyah bin Lago - Herwansyah Lago (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main objective of the study are as follows ; to design and analyze an electronically reconfigurable beamforming antenna at the centered frequency of 9.41 GHz ; to realize a high gain of the reconfigurable beam pattern antenna ; to achieve a wide tilting angle of the reconfigurable beamforming antenna.